2020
DOI: 10.1210/clinem/dgaa152
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Recurrence Following Lobectomy for Thyroid Cancer: Role of Thyroglobulin and Thyroglobulin Antibodies

Abstract: Background The use of thyroglobulin (Tg) and thyroglobulin antibodies (TgAb) for detecting disease recurrence is well validated following total thyroidectomy and radioiodine ablation. However, limited data are available for patients treated with thyroid lobectomy. Methods Patients who had lobectomy for papillary thyroid cancer followed for >1 year, with sufficient data on Tg and TgAb, including subgroup analysis for Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 17 publications
0
39
0
Order By: Relevance
“…Thyroid cancer is the most common endocrine cancer, and its incidence is increasing worldwide [1,2]. Nearly 20% of papillary thyroid cancer (PTC) patients who have no evidence of disease after initial treatment present with recurrence of disease during subsequent follow-up [3][4][5][6]. Although most recurrences in PTC are not fatal, they can be a great burden for patients, especially in a population with a high incidence rate for PTC, like Saudi Arabia [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid cancer is the most common endocrine cancer, and its incidence is increasing worldwide [1,2]. Nearly 20% of papillary thyroid cancer (PTC) patients who have no evidence of disease after initial treatment present with recurrence of disease during subsequent follow-up [3][4][5][6]. Although most recurrences in PTC are not fatal, they can be a great burden for patients, especially in a population with a high incidence rate for PTC, like Saudi Arabia [7].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, patients without recurrence were more likely to have Tg increase >20% over time. Another cohort study of 167 patients also observed a gradual increase in Tg levels over time [60]. In the absence of anti-Tg antibodies, average postoperative Tg levels were 14.7 ± 19.0 ng/mL.…”
Section: Long Term Follow-up and Detection Of Recurrences: Thyroglobumentioning
confidence: 82%
“…A further systematic review of 31 studies and 228,746 patients found that recurrence rates after thyroid lobectomy were slightly but significantly higher than after total thyroidectomy: 9% versus 7.4%, p = 0.001) [59]. Cancer recurrence in the contralateral lobe was observed in 4.8% of patients in the retrospective study by Ritter et al of 167 patients followed for an average of 6.5 years [60], with an additional 2.4% of patients with recurring lymph node metastases. Matsuzu et al reported a 6.5% rate of recurrence in the remaining thyroid and a 9.4% rate of recurrence in regional lymph nodes in 1088 patients followed for 25 years [38].…”
Section: Oncologic Considerations: Recurrence In the Contralateral Lomentioning
confidence: 95%
“… 77 However, the utility of these thresholds in appropriately stratifying patients after lobectomy has been challenged. 78 , 79 Further investigation is therefore needed to better define response criteria for patients treated with lobectomy.…”
Section: Postoperative Risk Stratificationmentioning
confidence: 99%